Akibat Hukum Terhadap Notaris Yang Membuat Akta Diluar Wilayah Jabatan Notaris Ditinjau Dari Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris - Rizky, Fahim Muhammad; Aminah, Aminah (Fakultas Syariah INSURI Ponorogo, 2023)
This writing aims to determine the legal consequences of a notary when making a deed outside the territory of his office. In this study, the authors used normative data collection techniques carried out by conducting a library search and supported by primary raw materials in the form of applicable laws and regulations, and secondary raw materials in the form of books, articles, and magazines, Pasal 17 letter a Law of The Republic of Indonesia Number 2 of 2014 concerning the Position of Notary. Determining “Notaries are prohibited from carrying out positions outside their territory of office” is in line with the prohibition of notaries making deeds outside their working area. If a notary draws up a deed outside his territory of office, he will be subject to sanctions contained in Pasal 17 Paragraph (1) of Law Number 2 of 2014 concerning the Position of Notary.